Key activity indicators: critical review and proposal of implementation criteria - Keegan, Richard (My University, 2022)
Purpose This paper discusses the concept, definition and usage of Key Activity Indicators (KAIs) and their integration within a Performance Measurement and Management system (PMM). Design/methodology/approach The actual definition and application areas of the KAIs are determined through a systematic literature review. Successively, a thorough definition of Key Activity Indicators is provided, along with a set of criteria for their deployment. Lastly, a case involving a Large Scale Retail Trade (LSRT) company is reported to report an example for guiding KAIs adoption. Findings This research shows that the scientific background concerning KAIs is still not mature. Moreover, the paper defines the role of KAIs for measuring operational activities and their possible connection with Key Performance Indicators (KPIs). Research limitations/implications Although KAIs have been introduced and discussed in the scientific literature; there is no evidence of criteria to deploy these indicators, leaving organizations without any guidance for their operational implementation. Practical implications From an academic standpoint, the study provides an overview of the usage of KAIs within the present scientific contributions, showing the advancements of this research field. From an industrial standpoint, the research proposes a set of criteria for the organizational deployment of KAIs. Originality/value The study investigates the concept of KAIs that, besides being originally conceived within World Class Manufacturing (WCM), has not received much attention in the scientific literature.
PUBLISHED
Keywords: Key Activity Indicators; Key Performance Indicators; Performance measurement and management; Operational Excellence Models; People Development; Human Factor; OPERATIONS MANAGEMENT; Strategic Management/ Strategy